Suicídio e psicoterapia: uma compreensão fenomenológica hermenêutica da experiência de pacientes que buscam pôr fim à vida. - Cabral, Glaucia Fernanda Soares (2021)
Suicide is a phenomenon that recently has attracted attention by the breadth of case numbers in the world, approximately 800,000 deaths per year, raising the creation of strategies and services that can help in prevention. In this scenario, psychologist has been called to produce understandings and actions, and psychotherapy is a psychological practice pointed out as a space of care and reception for those who think about ending their lives. From this horizon, this study has as a general objective to understand the possible resonances of psychotherapy in patients who sought this care in face of ideation stems or attempts to end life, and as specific objectives to problematize some conceptions constructed about suicide throughout history, present how psychological practices are positioned before patients who seek to end life and understand the experience of patients who sought psychotherapy before thought or attempt to end life. This is a qualitative study that privileges hermeneutic phenomenological orientation as a methodical path, carried out in the city of Teresina - PI, with the participation of four women who thought and/or tried to end their lives and sought psychotherapy for this reason. The resources used in the production of the data were the narrative interview and the field diary. The narratives of the collaborators and the researcher were understood from the resonances of Gadamer's Philosophical Hermeneutics. In this work, it was possible to follow the emergence of narrative threads that call into question how the pain of an existence emptied of senses, and which borders on the decision to end life, is understood and cared for in daily life. The diagnoses and medicalization were unveiled as norms that, when explaining and causing the numbness of pain, don’t accept the existential dimension. Psychotherapy was presented as a mode of care that opens to a possibility of welcoming and tensioning the issue between living and dying, however its clinical action may also incur a technical mode of care, resonating in the existence of the patient as a control and silencing of pain. It is necessary to question how Psychology has been in line with the current horizon of prevention, and that other possibilities of care could be delineated as an original and liberating listening to the patient and his sufferings.